Effect of Monetary Policy Announcements on Stock Prices in South Africa - Macalagh, Constance (Graduate School of Business (GSB), 2019)
The purpose of the monetary policy is to attain and sustain price stability in order to achieve balanced and sustainable economic development and growth. The stock market contributes to the growth of vital sectors of the economy and thus ultimately has an impact on the economy of a country. Prior to making investment decisions, investors consider the required rate of return, making stock prices largely sensitive to macroeconomic announcements. The purpose of the study is to define the extent to which the monetary policy rate announcements influence the behaviour of stock prices for firms that are listed on the Johannesburg Stock Exchange (JSE). A general conclusion from studies done in developed countries is that there is an inverse relationship between monetary policy and stock returns. The existing literature for developing economies, mainly Africa, focuses more on the relationship between long-term interest rates and stock prices and less on the policy rate effects on stock prices which have a number of limitations. According to literature, these limitations can be overcome by utilising the event study methodology. The event study methodology is known for using a short event period around the announcement of the policy rate in order to avoid limitations. In order to examine the impact of the policy rate announcement on the JSE, the study adopted the event study methodology to analyse data from October 2006 to September 2018. The data was collected from South African Reserve Bank publications and JSE daily trading reports. The results showed that abnormal returns were present for stock prices when there was a policy rate announcement. However, it was found that monetary policy rate announcements had no significant effect on companies listed on the JSE. The study concluded that there is no inverse relationship between the monetary policy announcement and the stock prices in South Africa. Monetary policy rate changes have an immediate effect on commercial banks and because of this, it assumed that the monetary policy rate announcement will have a greater impact on commercial bank stock prices than it would have on non-bank stock prices. The results from this study did not confirm this assumption as the bank stocks were not impacted more by the monetary policy rate announcement than the non-bank stocks were. This paper further confirms the finding of studies done in developing countries where it is found that policy rate actions do not significantly influence the stock markets in developing countries and more importantly those within Sub-Saharan Africa.